2011
DOI: 10.1007/s10482-011-9619-5
|View full text |Cite
|
Sign up to set email alerts
|

Fructose increases the resistance of Rhodobacter capsulatus to the toxic oxyanion tellurite through repression of acetate permease (ActP)

Abstract: The highly toxic oxyanion tellurite (TeO(3) (2-)) enters the cells of the facultative photosynthetic bacterium Rhodobacter capsulatus through an acetate permease. Here we show that actP gene expression is down-regulated by fructose and this in turn determines a strong decrease of tellurite uptake and a parallel increase in the cells resistance to the toxic metalloid (from a minimal inhibitory concentration of 8 μM up to 400 μM tellurite under aerobic growth conditions). This d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…After 15 min exposure to HAuCl 4 or K 2 TeO 3 , most part (90%) of the metal(loid) remains in the extracellular fraction. While tellurite entrance is mediated mainly by the phosphate transporter PitA and/or by the acetate transporter ActP (Borghese et al, 2011; Elías et al, 2012, 2015), that of gold would be mediated by sulfhydryl group-rich membrane proteins (Snyder et al, 1986). As mentioned, about 10% of the toxicants enter the cell, which could generate an adaptive response thus enabling it to better respond to toxicant-mediated damage in aerobic (gold) or anaerobic growth conditions (tellurite).…”
Section: Discussionmentioning
confidence: 99%
“…After 15 min exposure to HAuCl 4 or K 2 TeO 3 , most part (90%) of the metal(loid) remains in the extracellular fraction. While tellurite entrance is mediated mainly by the phosphate transporter PitA and/or by the acetate transporter ActP (Borghese et al, 2011; Elías et al, 2012, 2015), that of gold would be mediated by sulfhydryl group-rich membrane proteins (Snyder et al, 1986). As mentioned, about 10% of the toxicants enter the cell, which could generate an adaptive response thus enabling it to better respond to toxicant-mediated damage in aerobic (gold) or anaerobic growth conditions (tellurite).…”
Section: Discussionmentioning
confidence: 99%
“…In R. capsulatus it has been shown that a mutant impaired in tellurite uptake became highly resistant to the oxyanion and the uptake defect was restored by the acetate permease actP2 gene [17], supporting an earlier observation indicating that acetate inhibits tellurite uptake in R. capsulatus cells, as both anions compete for the same permease [18]. This evidence led to the proposal that in R. capsulatus tellurite enters the cell mainly through the acetate transport system (RcActP2) [17,19]. Early work in E. coli cells [20] reported that phosphate transport mutants were characterized with higher resistance to TeO 3 2-and that the oxyanion was a potent inhibitor of A C C E P T E D M A N U S C R I P T which identifies in the homodimeric structure of ActP2 a signature of the strong tellurite uptake activity shown by this permease, namely a 15 amino acids insert that is missing in all ActP1 type permeases.…”
Section: -mentioning
confidence: 61%
“…pRB71 (Km r ) is a pRB3 derivative carrying a translational fusion of the actP2 operon from R. capsulatus to the reporter gene lacZ [19]. pRK415 (Tc r ) is a broad-host-range cloning plasmid for…”
Section: Plasmidsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that acetate and propionate were transported by the same transport system but further confirmation is required as Candidatus Competibacter phosphatis appeared to have different transporters for the two solutes [21]. Another acetate permease, ActP of Rhodobacter capsulatus , was produced around 1.5 folds more in acetate- than in pyruvate-grown cells [22]. This indicated that the regulations of various acetate-transport systems in different bacteria are likely to be different and should be compared cautiously.…”
Section: Discussionmentioning
confidence: 99%